2021
DOI: 10.3389/fvets.2021.609348
|View full text |Cite
|
Sign up to set email alerts
|

Cecal Microbiota Modulates Fat Deposition in Muscovy Ducks

Abstract: Ducks with the same genetic background vary greatly in their adiposity phenotypes. The gut microbiota plays an essential role in host physiological development and metabolism including fat deposition. However, the association of the gut microbiota with the lipogenic phenotype of ducks remains unknown. In this study, we investigated the cecal microbiota of adult Muscovy ducks and the correlation of the cecal microbiota with fat phenotypes. A total of 200 Muscovy ducks were selected from a population of 5,000 Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
1
16
1
Order By: Relevance
“…These bacteria are considered as dominant players in the degradation of diverse polysaccharides and fibers (59,60). Ruminiclostridium_5 and [Ruminococcus]_torques_group were found to be related to fat deposition (52,61), while Ruminococcaceae UCG-014 was linked to the maintenance of gut health and was able to degrade diverse cellulose and hemicellulose with enzymatic capability (62). The genera Blautia and Butyricicoccus were also recognized as cecal biomarkers in our study.…”
Section: Discussionmentioning
confidence: 55%
“…These bacteria are considered as dominant players in the degradation of diverse polysaccharides and fibers (59,60). Ruminiclostridium_5 and [Ruminococcus]_torques_group were found to be related to fat deposition (52,61), while Ruminococcaceae UCG-014 was linked to the maintenance of gut health and was able to degrade diverse cellulose and hemicellulose with enzymatic capability (62). The genera Blautia and Butyricicoccus were also recognized as cecal biomarkers in our study.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, the relative abundances of Parabacteroides , Ruminococcus torques group , Clostridia UCG-014 , Methanobrevibacter , Parasutterella, Candidatus Saccharimonas , and Streptococcus were significantly higher in the ZG than in FG. Study has reported that the Ruminococcus torques group was significantly correlated with fat deposition in ducks [ 32 ]. Therefore, the ZG may have a better fat deposition ability than the FG.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we reported that E2 correlated with the g__Ruminococcus_torques_group . The g__Ruminococcus_torques_group , which belongs to the family Lachnospiraceae , was found to be related to fat deposition [ 38 , 39 ]. A positive association of abdominal fat and subcutaneous fat thickness with f__Lachnospiraceae abundance was observed in the broilers [ 40 ].…”
Section: Discussionmentioning
confidence: 99%